Hardware-virtualization-based software compatibility analysis method and its applications - Xiangjiang Hu; Bo Cong; Zhendong Xi; Kang Li (2014 IEEE International Conference on Progress in Informatics and Computing, 2014)
This paper proposes the concept of application software compatibility and highlights its important implication to high-reliable information application system. Aiming at the issues of typical of software compatibility, an analysis method of software compatibility is presented based on hardware virtualization. Compatibility of two typical information security software is analyzed and the results are evaluated. The proposed analysis method can also be an illumination in other scenarios.